Space use, movements, and survival of pygmy rabbits in response to construction of a large pipeline. (21st September 2018) - Edgel, Robert J.; Larsen, Randy T.; Whiting, Jericho C.; Mcmillan, Brock R.
ABSTRACT: Little is known about how energy development affects pygmy rabbits ( Brachylagus idahoensis ). We quantified space use, movements, and survival of pygmy rabbits before and after construction of the Ruby Pipeline in Utah, USA, from 2010 to 2012. For 18 rabbits captured in and near the pipeline right‐of‐way (ROW) 1 month before construction, 95% kernel home ranges and 50% core areas were ≥3.7 times smaller 1 month after construction. Additionally, those 18 pygmy rabbits shifted the center of 50% core areas away from the ROW following construction ( x ¯ = 34 m, SD = 36.3, range = −11 to 119 m). Also, 95% kernel home ranges and 50% core areas for 40 rabbits captured in and near the ROW and monitored for 18 months after construction were ≥2.6 times smaller than estimates of similar space use for 25 rabbits in a reference area during the same time. Only 3 of 22 rabbits captured in or near the ROW before construction began crossed the ROW during the 18 months following construction. Weekly estimates of survival for rabbits in or near the ROW were similar before, during, and after construction; and similar to survival rates for rabbits in a reference area. Our results will contribute to biologists' understanding of the influence of habitat removal and fragmentation associated with the construction of linear features on pygmy rabbits and their habitat. © 2018 The Wildlife Society. Abstract : Little is known about how energy development affects pygmy rabbits. We documented significant decreases in space use and shifting of core areas by pygmy rabbits away from construction activities of the Ruby Pipeline.